Extracellular microRNAs modulate human microglial function through TLR8 - Weidling, Hannah; Motta, Edyta; Kuhrt, Leonard D.; Krüger, Christina; Figueiredo, Caio Andreeta; Wallach, Thomas; Frahm, Silke; Diecke, Sebastian; Wolf, Susanne A.; Kettenmann, Helmut; Lehnardt, Seija (Frontiers in Immunology, 2025)
ObjectiveMicroRNAs (miRNAs) are abundantly expressed in the brain and are specifically dysregulated in central nervous system (CNS) diseases. They act as post-transcriptional gene regulators but can also serve as ligands for Toll-like receptors (TLRs). This study aims to investigate CNS disease-associated miRNAs as signaling molecules for human microglia.MethodsUsing a machine learning algorithm and the disease-linked database PhenoMiR, we identified Alzheimer’s disease (AD)- and glioma-associated miRNAs as ligands for TLR7 and TLR8. Expression of human TLR7 and TLR8 in iPSC-derived human microglia-like cells (iMGLs) was validated by RT-qPCR. Using ELISA, scratch assay, and FACS, we investigated the miRNAs’ potential to modulate iMGL function, including cytokine release, motility, and phagocytosis, respectively. The selective human TLR8 antagonist CU-CPT9a was used to determine the role of this receptor in miRNA-induced modulation of human microglial activity. Co-cultures of iMGLs and iPSC-derived human cortical neurons (iNeurons) were analyzed by Neurotrack imaging to assess the effects of miRNAs on human neurites.ResultsWe identified AD- and glioma-associated miR-9-5p, miR-132-5p, miR-340-3p, miR-30e-3p, miR-501-3p, and let-7b as ligands for human TLR7 and TLR8. Exposure of iMGLs to select miRNAs, including miR-9-5p, miR-132-5p, and miR-340-3p, led to interleukin-6 (IL-6) and tumor necrosis factor (TNF) mRNA expression and protein release in a sequence-dependent fashion. Also, these miRNAs acting as signaling molecules, modulated iMGL motility and phagocytosis activity. The miRNA-induced effects on iMGLs were abolished by CU-CPT9a. Extracellular delivery of miR-132-5p and miR-9-5p to co-cultures of iNeurons and iMGLs resulted in reduced neurite length.DiscussionOur data establish that distinct CNS disease-associated miRNAs serve as signaling molecules for human microglia via TLR8, thereby controlling the diverse microglial functions and modulating the neuroinflammatory response.